Prevalence of primary dysmenorrhea, its intensity, impact and associated factors among female students' at Gondar town preparatory school, Northwest Ethiopia - Abere Woretaw Azagew; Destaye Guadie Kassie; Tarkie Abebe Walle (BMC, 2020)
Abstract Background Primary dysmenorrhea is defined as a crampy pain in the lower abdomen before or during the menstrual period in the absence of any pelvic pathology. It is the leading motherhood problem worldwide but there is limited evidence on the prevalence of primary dysmenorrhea in the study area as well in Ethiopia. Researching primary dysmenorrhea helps to focus on the treatment plan. The study aimed to assess the prevalence, intensity, impact, and associated factors of primary dysmenorrhea among female students at Gondar town preparatory school. Methods A cross-sectional study design conducted among female students at Gondar town Preparatory School from May 1-10/2017. A total of 459 study participants were used. A simple random sampling technique was used to select study participants. A self-administered structured questionnaire was employed. Epi Info version 7 and SPSS version 20 were used for data entry and analysis respectively. A binary logistic regression model was computed. Variables having a p-value < 0.05 in the multivariate logistic regression model were considered as statistically significant. Results A total of 459 female students participated in the study with a response rate of 96.29%. The prevalence of primary dysmenorrhea among female students was found to be 64.7% (95% CI; 60.2-69.2%). Around 61% reported moderate intensity of menstrual pain and 50.7% complain about lower abdominal pain. Sixty-five percent of study participants reported that absenteeism from school was the impact of menstrual pain. Having irregular monthly menstrual cycle (AOR = 1.70, 95% CI; 1.02, 2.84) and positive family history of dysmenorrhea (AOR = 5.19, 95% CI: 3.21, 8.37) were significantly associated with primary dysmenorrhea. Conclusions The prevalence of primary dysmenorrhea was found to be high. Having an irregular monthly menstrual cycle and a positive family history of dysmenorrhea were determinants of primary dysmenorrhea.